Replacement model of phase change building materials for heat load calculation. Issue 2 (1st April 2020) - Serikawa, Mao; Satoh, Makoto; Mae, Masayuki
Abstract: Phase change materials (PCMs) may contribute to room temperature stability and heat load reduction. This research proposes a method to calculate heat load using a PCM replacement model for a thermal storage wall. Regarding the replacement of PCM with internal thermal mathematical models, the replaced PCM temperature and room temperature are related. The method to replace PCM in adjoining rooms is based on the heat transfer coefficient, heat transmission coefficient, solar absorptance on the surface of a wall, ceiling, or floor, etc. We compare the results of the proposed replacement model of room temperature and heat load to a detailed heat load calculation. Abstract : This research proposes a method to calculate heat load using a replacement model of phase change materials (PCM) in a wall. Regarding the replacement of PCM with internal thermal mathematical models, the replaced PCM temperature and room temperature are related. We compare the results of the proposed replacement model of room temperature and heat load to a detailed heat load calculation.